Cerebrospinal Fluid Protein Level and Nerve Conduction Study as Short-Term Prognostic Marker of Guillain Barré Syndrome (Bangladesh Journal of Neuroscience, 2018)
Background: Guillain Barré Syndrome (GBS) diagnosis is based on a combination of clinical features, Nerve conduction studies (NCS) and analysis of the cerebrospinal fluid (CSF) which eventually assist in monitoring disease progression as well as the efficacy of immunotherapy. The main objective of this study was to determine the relation of CSF protein level and nerve conduction study with short-term prognosis of GBS patients.Methods: This observational study was carried out in the Department of Neurology and Medicine, Dhaka Medical College Hospital, Dhaka during the period August, 2017 to July, 2018. Total 50 patients suffering from GBS were enrolled in this study. Lumber puncture (LP) and NCS were done at day 10 of symptom onset.Results: In this study majority (87.5%) of the patients had GBS Disability score